Sequence diversity in the large subunit of RNA polymerase I contributes to Mefenoxam insensitivity in Phytophthora infestans. (14th April 2014) - Randall, Eva; Young, Vanessa; Sierotzki, Helge; Scalliet, Gabriel; Birch, Paul R. J.; Cooke, David E. L.; Csukai, Michael; Whisson, Stephen C.
Summary Phenylamide fungicides have been widely used for the control of oomycete‐incited plant diseases for over 30 years. Insensitivity to this chemical class of fungicide was recorded early in its usage history, but the precise protein(s) conditioning insensitivity has proven difficult to determine. To determine the genetic basis of insensitivity and to inform strategies for the cloning of the gene(s) responsible, genetic crosses were established between Mefenoxam sensitive and intermediate insensitive isolates of Phytophthora infestans, the potato late blight pathogen. F1 progeny showed the expected semi‐dominant phenotypes for Mefenoxam insensitivity and suggested the involvement of multiple loci, complicating the positional cloning of the gene(s) conditioning insensitivity to Mefenoxam. Instead, a candidate gene strategy was used, based on previous observations that the primary effect of phenylamide compounds is to inhibit ribosomal RNA synthesis. The subunits of RNA polymerase I (RNApolI) were sequenced from sensitive and insensitive isolates and F1 progeny. Single nucleotide polymorphisms (SNPs) specific to insensitive field isolates were identified in the gene encoding the large subunit of RNApolI. In a survey of field isolates, SNP T1145A (Y382F) showed an 86% association with Mefenoxam insensitivity. Isolates not showing this association belonged predominantly to one P. infestans genotype. The transfer of the 'insensitive' allele of RPA190 to a sensitive isolate yielded transgenic lines that were insensitive to Mefenoxam. These results demonstrate that sequence variation in RPA190 contributes to insensitivity to Mefenoxam in P. infestans.